Pie academy : master the perfect crust and 255 amazing fillings, with fruits, nuts, creams, custards, ice cream, and more : expert techniques for making fabulous pies from scratch - Haedrich, Ken, 1954- (Storey Publishing, 2020)
"Discover recipes for all types of crusts and pastry, including gluten-free, whole wheat, and extra-flaky. Learn about the best tools and gadgets to make dough and fillings. Step-by-step instructions with photos make it easy for bakers of all levels"--